Radiological features of endocrine orbitopathy involving lacrimal gland - V. G. Likhvantseva; T. N. Safonova; N. Y. Sviridenko; O. A. Gontyurova; E. A. Rudenko; V. A. Vygodin (Oftalʹmologiâ, 2014)
According to orbit computer tomography, lacrimal gland is involved in autoimmune process in 26.8% of patients with Graves’ orbitopathy. A short orbit is a predisposing factor of the lacrimal gland (LG) involvement in the autoimmune process. In addition to increasing of the size of the lacrimal gland, formed thickening of the optic nerve in 1 cm from the eye posterior pole (in 60% of cases), the increase in x-ray density of orbital portions of optic nerve, proved «shortening» of length in axial projection with reliable reduc- tion of length to width ratio (with increase in width at the same time) up to 5.8±0.2 are roentgenological features of this сlinical form. Change of spatial topography in orbit with reduction of the conversion rate was associated with increased rate of optic neuropathydevelopment.